EFISIENSI PENGGUNAAN BIBIT DAN PUPUK PADA USAHA TANI TANAMAN BUAH NAGA DI KEACAMATAN SAMARINDA UTARA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this research is to determine the effect of seed and fertilizer to the number of dragon fruit production in the District of North Samarinda and to know and to analyze which variables are the dominant influence on the amount of dragon fruit production in the district of North Samarinda. The data used in this analysis is the primary data obtained from the results of observation, interviews and questionnaires then calculated using a multiple linear regression analysis and processed using SPSS (stastical Programme For Science) version 20. Based on test results simultaneously obtained seeds and fertilizers positive and significant effect on the number of dragon fruit production in the district of North Samarinda. Then partially to seed positive and significant effect, while fertilizer but a significant negative effect on the number of dragon fruit production. Based on these results it can be concluded that the seed is more dominant influence on the amount of dragon fruit production in the district of North Samarinda.Keywords: Seeds, Fertilizers and Production